Water Resources Management at Raden Intan Islamic State University, Indonesia - Wan Jamaluddin; Suci Wulan Pawhestri; Nanang Supriadi; Bambang Budiwiranto (Journal of Sustainability Perspectives, 2023)
UIN Raden Intan Lampung is an Islamic university located at the southernmost tip of Sumatra. The area receives a rainfall ranging between 77-317 mm3 in 2022, and this rainfall must be harnessed and conserved as water reserves for daily needs. The university has a total area of 45 hectares, and it is home to a population of 34,482 individuals. The soil texture in the UIN Raden Intan Lampung campus area is predominantly clay, and the dense soil particles make it challenging to absorb water. Consequently, measures are required to regulate soil moisture levels to facilitate optimal water absorption. One strategy to preserve the water supply on campus is the construction of artificial ponds that capture rainwater. Ten such ponds have been built, covering 21.54% of the total green open space owned. Furthermore, around 8,000 biopore infiltration holes have been installed to maintain groundwater availability and improve soil fertility. The campus also conducts campaigns to promote water conservation and uses water-saving equipment technology. Treated wastewater from ablution activities in mosques is employed for secondary needs such as fish farming activities and irrigation. Ultimately, the preservation of water resources on campus must be sustainable, given the large population of people who depend on water for their daily needs, and ensuring water availability for the future is critical.